The Skarù·ręʔ (Tuscarora) Food Forest Project—Reconciliation in Sustainable Agriculture Research and Education through Cross-Cultural Agroforestry Demonstration - Bosco, Samantha; Thomas, Bradley (Ethnobiology Letters, 2023)
Temperate nut trees have long been utilized in eastern North America, providing high quality food, durable materials, and contributing to multispecies relationships across geographic and cultural landscapes. While not widely consumed today, renewed interest in temperate nuts such as hybrid chestnuts and hazelnuts, are part of efforts to realize nature-based solutions to climate change, which include multifunctional agroforestry systems. Indigenous peoples’ contributions to agroforestry and climate resilience are substantial, however sustainable agricultural research often overlooks critical social justice implications underlying the history of colonization in settler nations, including dispossessed land and appropriated Indigenous crops. As one of the most nutritionally dense plant-based foods, nuts were important components of Haudenosaunee foodways. Archaeological, ethnographic, and historical-ecological evidence indicate that the Haudenosaunee subsistence and settlement dynamics transformed cultural landscapes favoring such nut trees. The Skarù·ręʔ (Tuscarora) Food Forest was a community-based project demonstrating contemporary contributions of nut trees to Indigenous food systems in ancestral Haudenosaunee territories, today known as New York State. While domesticated crop polycultures (i.e., the Three Sisters) are iconic of Haudenosaunee horticultural ingenuities, temperate nuts are lesser-known woodland foods that can additionally contribute to food and language revitalization efforts within contemporary Haudenosaunee territories. Here we discuss theories and praxes informing community engaged approaches at the Skarù·ręʔ Nation. By addressing social justice concerns within agricultural science, we demonstrate how the Skarù·ręʔ Food Forest Project can provide a methodological testing ground for reconciliation-based and decolonial participatory action research that expands ongoing food sovereignty, community health, and education initiatives.